Gendering the Informal Tourism Sector toward Inclusive and Sustainable Growth: The Case Study of Boracay Island - Jean Clarisse T. Carlos; Marie Jel D. Bautista; Eylla Laire M. Gutierrez (Philippine Institute for Development Studies (PIDS), 2023)
Boracay Island, Malay is one of the most popular tourist destinations in the Philippines. Over the years, its sustained growth as a top tourist destination has been substantially supported by the island's informal tourism sector-that is primarily women dominated. While tourism products and services are provided by both men and women, differences are observed in their occupational choices and the options made available for them. For this reason, concerns about the sustainability of tourism development vis-à-vis gender inclusivity have been raised. In an attempt to bridge this gap, this study investigated the involvement of women in the informal tourism of Boracay Island. This study specifically looked into their working conditions, the challenges and issues they face, along with the national policies that govern and regulate their participation in the informal economy. By utilizing the Women's Economic Empowerment Framework, the macro, meso, and micro dimensions of women's involvement in the informal tourism economy was analyzed. To do so, the authors conducted key informant interviews in three phases: first, with members of the local government units (LGUs) of the Municipality of Malay and the Boracay Island; second, with women informal workers serving in the food and beverages, souvenirs, excursions, and services sector in the Boracay Island; finally, with experts in tourism and informal economy at the national level. Findings of the study suggest that informal workers in the Island are organized, recognized, and registered under the LGU. Despite attempts to facilitate their transition to the formal economies, these women workers were found to prefer to operate under the informal economy for two reasons: first, their educational background which forces them to engage in informal work to help provide for their families; second, their personal choice to engage in informal work given the flexible and convenient work arrangements it offers them. For these workers, concerns about their dependence to the seasonality of tourism activities prevailed. Policy recommendations are outlined to provide a better understanding of women's involvement in the informal economies in Boracay Island.
Keywords: 330; tourism; informal sector; gender and development; value chain analysis; inclusive growth